Amended description of the Sumatran endemic Dendrobium bandii (Orchidaceae) with notes on its conservation status and ecology - Naive, Mark Arcebal K.; Yudistira, Yuda Rehata; Victoriano, Malcolm; Ormerod, Paul (Lankesteriana: International Journal on Orchidology, 2021)
Dendrobium bandii is a poorly known species endemic to the island of Sumatra, Indonesia. We studied living specimens and we provide here an amended description of the species, colour photographs, as well as information on distribution, ecology, and its provisional conservation status.